JBRMR 2018
DOI: 10.24052/jbrmr/v12is02/rbtaaabitmrotataaamrocn
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the advertising appeal and behavioral intention: The mediating role of the attitude towards advertising appeal and moderating role of cultural norm

Abstract: Studies IntroductionStudies have indicated that not only attitude predict the behavioral intention, in fact, recent studies based on planned behavioral intention framework have outlined many antecedents of behavioral intention (Kenney and Khanfar, 2009). Therefore, scholar such as Walden (2012) has called more studies to identify the underlying attitude process variables linking advertising appeal and behavioral outcomes in advertising. To date, the direct and indirect effect of attitude on behavioral intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Although, it is widely demonstrated that more positive attitudes toward commercials are linked to an increase in purchase intention (Raza, Bakar, & Mohamad, 2018) (Rodero et al, 2013) or from 19 to 65 years old (Whipple & McManamon, 2002). The former study extrapolated the findings to other age groups; and the latter one did not find age differences in the results.…”
Section: Discussionmentioning
confidence: 81%
“…Although, it is widely demonstrated that more positive attitudes toward commercials are linked to an increase in purchase intention (Raza, Bakar, & Mohamad, 2018) (Rodero et al, 2013) or from 19 to 65 years old (Whipple & McManamon, 2002). The former study extrapolated the findings to other age groups; and the latter one did not find age differences in the results.…”
Section: Discussionmentioning
confidence: 81%
“…To improve the productivity of attitude, studies have suggested determining the antecedent of the attitude, which remains minimal. Moreover, some studies explained factors such as information seeking and clarified that attitude does not solely predict the intention [62]. In the context of the TPB communication, scholars argued that digital advertising with the underlying mechanism of attitude could be examined due to its persuasive nature.…”
Section: Effect Of Digital Advertising On Online Purchase Intentionmentioning
confidence: 99%
“…In addition, literature suggests that advertisement messages contain informational and emotional cues that activate the evaluation process (Raza et al, 2018). The more an individual finds that these cues correspond with his or her prevailing experiences or knowledge, the more likely will the individual be to acquire the behaviour in question.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Nelson et al (1997) noted that distinct representations of a policy controversy produce distinct responses by manipulating the relevance of particular values to the conflict at hand. Literature clearly indicates that if an advertisement message does not appeal to a person’s ideology or value, it stands the risk of being rejected, as it seems like there is no positive content, appearing to attack the values or ideologies of the recipient (Cui et al, 2012; Raza et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%